The effect of anxiety and depression levels of children with celiac disease on quality of life - Belpınar, Ayşe; Dağ, Yeliz Suna; Arıcıoğlu Sülün, Ayşe; Yayan, Emriye Hilal; Varol, Fatma İlknur (W.B. Saunders, 2023)
Purpose: This study was conducted to examine the effect of anxiety and depression levels on quality of life in children with celiac disease. Design and method: This descriptive and correlational study was conducted with 98 children diagnosed with celiac disease who applied to the pediatric outpatient clinic of a university hospital in Eastern Anatolia between September 2021 and August 2022. Data were collected using the State-Trait Anxiety Scale, Depression Scale, and Quality of Life Scale through face-to-face interviews conducted by the researchers. Percentage distribution, mean, independent samples t-test, Pearson correlation analysis and regression analysis were used to analyze the data. Results: It was found that 62% of the participant children were female and their mean age was 11.69 ± 4.15 years. The mean scores of state anxiety, trait anxiety, depression and quality of life of children with celiac disease were 42.46 ± 5.42 (high), 43.83 ± 7.08 (high), 23.37 ± 4.79 (high) and 43.67 ± 19.67 (low), respectively. Regression analysis revealed that anxiety had a statistically significant relationship with quality of life. Conclusions: It was found that children with celiac disease experienced high levels of depression and anxiety along with physical functionality and psychosocial health problems and this negatively affected their quality of life. It is recommended that children with celiac disease should be followed up and supported psychosocially. Practice implications: That healthcare professionals can contribute to reducing the depression and axienty and improving the quality of life by strengthening the social support systems of childrens with celiac disease. © 2023 Elsevier Inc.
Keywords: Anxiety; Celiac disease; Child; Depression; Quality of life